Mixed Bacteriological Isolation Percentages from the Uterus of Cows Slaughtered due to Infertility - Risvanli, Ali; Kalender, Hakan; Safak, Tarık; Yüksel, Burak Fatih; Karagulle, Burcu; Yılmaz, Oznur; Kilinc, Mehmet Akif (The Running Line, 2023)
Background: Intrauterine mixed infections are an important problem in cattle breeding. In this study, we aimed to determine the mixed bacteriological isolation rates from the uterus of cows with clinical metritis and to reveal the relationships between the bacteria that isolated together.Methods: For this purpose, sterile swabs were taken from 490 uterus obtained from cattle slaughtered due to infertility in three slaughterhouses and used them to perform microbiological tests. After evaluating the data, it was determined that the bacterial isolation rate from uterus with clinical metritis was 76.14% (n = 268).Results: The rates for 1, 2, 3, 4, and 5 bacteria isolated from the uterus with clinical metritis were 48.13%, 33.96%, 15.30%, 2.24%, and 0.37%, respectively. The isolation rates for Trueperella pyogenes, Fusobacterium necrophorum, and Escherichia coli alone from the uterus with clinical metritis were 27.08%, 28.00%, and 16.51%, respectively. In uterus with clinical metritis, Staphylococcus aureus (16.67%) was the most commonly isolated bacteria with T. pyogenes, Clostridium spp. (16%) co-isolated with F. necrophorum, and coagulase-negative staphylococci (16.51%) and Bacillus spp. (16.51%) were detected with E. coli.Conclusion: As a result, it was concluded that when evaluating the microbiological results for cows with clinical metritis, mixed infections should be taken into more consideration, and the characteristics of the bacteria that isolate together should be considered during the treatment of mixed infections.Keywords: Cattle; Uterine; Isolation; infertility
Keywords: Uterine; Cattle; infertility; Isolation